2011
DOI: 10.1007/s10096-011-1283-1
|View full text |Cite
|
Sign up to set email alerts
|

stx genotype and molecular epidemiological analyses of Shiga toxin-producing Escherichia coli O157:H7/H− in human and cattle isolates

Abstract: The relationship between human diseases caused by infection with Shiga toxin (Stx)-producing Escherichia coli (STEC) O157 strains and O157 strains isolated from cattle was investigated in an area where stockbreeding is prolific. For this purpose, the stx genotypes, the molecular epidemiological characteristics of 268 STEC O157 strains including 211 human-origin strains and 57 cattle-origin strains, and clinical manifestations of 210 STEC-infected people were analyzed. Of 211 human-origin strains, 92 strains (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2011
2011
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…So, stx2-producing strains are more relevant to clinical disorders including HUS than stx1 (Paton & Paton, 2002;Bai et al, 2015). In the present study most of the isolates possessed stx2 which is in accordance with the results reported in Argentina (Blanco et al, 2004), China (Zheng et al, 2005;Koitabashi et al, 2008), Japan (Kawano et al, 2012) and Denmark (Nielsen et al, 2002). Lower prevalence rates were reported in Brazil (1.35%; Martins et al, 2011) and India (11%; Khan et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…So, stx2-producing strains are more relevant to clinical disorders including HUS than stx1 (Paton & Paton, 2002;Bai et al, 2015). In the present study most of the isolates possessed stx2 which is in accordance with the results reported in Argentina (Blanco et al, 2004), China (Zheng et al, 2005;Koitabashi et al, 2008), Japan (Kawano et al, 2012) and Denmark (Nielsen et al, 2002). Lower prevalence rates were reported in Brazil (1.35%; Martins et al, 2011) and India (11%; Khan et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…In another outbreak caused by non-O157 STEC, infected cases including 43 deaths have been recently reported in the European Union (ECDC, 2011). Furthermore, although the pathogenicity mechanisms of STEC are not yet fully understood, Shiga toxin genes 1 and 2 (stx1 and stx2) are the main factors for virulence properties in STEC pathogenesis and development of clinical symptoms (Kawano et al, 2012;Bai et al, 2015). Moreover, previous literature reports indicated that other virulence factors may play significant roles in the pathogenicity of this pathogen such as intimin which is encoded by the chromosomal gene eaeA and is responsible for intimate attachment of STEC to intestinal epithelial cells (Kaper et al, 1998;Bastos et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in line with reports from other regions in Norway (L. T. Brandal, A. L. Wester, H. Lange, I. Løbersli, B.-A. Lindstedt, G. Kapperud, and L. Vold, unpublished data) and other countries (5,(45)(46)(47), our results support the notion that infections with STEC strains that do not belong to common STEC serogroups and lack eae and/or stx 2a even if stx 1 is present represent a low risk for HUS development. Therefore, based on the results from the present study, it seems safe to suggest a classification of stx 1 -positive, stx 2 -negative STEC strains with a low risk for HUS development.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have suggested that E. coli O157:H7 strains that similarly carry stx 2c but not stx 2a may be less pathogenic than strains that carry stx 2a (27)(28)(29). For example, strains carrying stx 2c are frequently found in isolates from both cattle and healthy people (30,31) whereas stx 2a strains are more frequently isolated from patients with serious symptoms (32). Our results support this association: 81.9% of the clinical isolates in this study tested positive for stx 2a versus 51.8% of cattle isolates.…”
Section: Discussionmentioning
confidence: 99%